Woman Empowerment through Agriculture and Domestic of Diasporic Woman in Keluarga Bahagia di Jerman’s YouTube Channel - Poetry Salsabila Nurrania; Muhammad Miqdad Rojab Munigar (Jurnal Komunikasi, 2025)
This research examines a new form of epistolary performed by an Indonesian-German diasporic woman named Trisna Keller through her YouTube channel entitled “Keluarga Bahagia di Jerman”. This research also aims to explore how gardening activities in the home garden, as part of domestic routine, can serve as a narrative strategy shaping identity and mediating cultural negotiations in the lives of Indonesian diaspora women. This research employs a narrative analysis method using an epistolary literary framework and postcolonial concepts to analyze phenomena displayed on social media. Trisna Keller's vlog in Keluarga Bahagia di Jerman is read as a form of epistolary in digital space that articulates personal experiences of memory, emotion, and cultural heritage through digital space. The exploration of nostalgia for tropical plant products combined with their adaptation to subtropical environments becomes a bridge between Indonesia and Germany. This research argues that Trisna Keller's performance in cultivating vegetables and fruits in Germany through the seeds she brought from Indonesia functions as a symbolic act of remembrance as well as a form of shifting Western colonial discourse. This becomes a form of politics that is implicit in shifting the historical form of colonialism towards the mechanism of botanical negotiation. While botanical negotiations once required serious scientific exploration, can now be simplified into domestic values and hobby-based practices expressed through social media.